Sports Science : a complete introduction - Simon Rea (Revised and updated 2nd edition., 2023)
"Human beings have always sought ways to gain a competitive edge over their opponents, but sports science is a relatively young discipline. So what is it all about, and how can it help athletes perform better? Sports science is the application of scientific principles to explain sporting phenomena and provide a basis for improving the performance of teams and individuals. In this comprehensive yet easy-to-use introduction, you will learn everything you need to know about it in one place, including the key research and current knowledge, providing you with a well-informed starting point in your study of this fascinating subject. The focus of the book is on the three disciplines of biomechanics, physiology and psychology: Biomechanics: using mechanical principles to understand human movement and how the human body interacts with equipment and apparatus; Physiology: using biological sciences to investigate how the body responds to exercise and training; Psychology: using psychological principles to provide answers to questions about human behaviour in sports settings. This new edition has been updated to include case studies to show what you can do with a sports science degree and advice on how to prepare for careers where sports science knowledge is used. It includes chapters on the key systems in the body - skeletal, muscular, cardiovascular and nervous - as well as covering sports nutrition and planning research in sport. Whether you are a student, interested in sport and sport performance as a professional practice, or involved in sport at any level, Sports Science: A complete introduction is your go-to guide"--Publisher's description.